Zwitterion formation and subsequent carboxylate–pyridinium NH synthon generation through isomerization of 2-anilinonicotinic acid. Issue 40 (27th September 2018) - Yue, Pengyun; Dong, Caiqiao; Zhang, Mingtao; Xu, Danrui; Parkin, Sean; Li, Tonglei; Li, Conggang; Yu, Faquan; Long, Sihui
Abstract : Structural isomerization of 2-anilinonicotinic acids to 4-anilinonicotinic acids leads to an increase of Δp K a, thus leading to the formation of a carboxylate–pyridinium NH dimer in the solid state. Abstract : Through structural modification of 2-anilinonicotinic acid by isomerization, the Δp K a between the carboxylic acid and pyridinium NH increased dramatically over the threshold to form zwitterions in the newly designed 4-anilinonicotinic acids. This in turn led to the formation of a hydrogen bond between carboxylate and pyridinium NH, and the absence of two commonly observed synthons, i.e., the acid–acid homosynthon and acid–pyridine heterosynthon. The new synthon has a stronger hydrogen bond than the acid–acid homosynthon and the acid–pyridine heterosynthon, as suggested by theoretical calculations. This, together with the much larger Δp K a, explains its formation.